High average power few-cycle laser for ELI-ALPS - Hädrich, S.; Eidam, T.; Just, F.; Shestaev, E.; Hoff, D.; Kienel, M.; Becker, N. C.; Eilenberger, F.; Klenke, A.; Müller, M.; Gottschall, T.; Drozdy, A.; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2018)
We present a characterization and an analysis of the scaling potential for the ELI-ALPS HR1 laser system emitting 100 W of average power, 1 mJ of pulse energy and <7 fs CEP-stable pulses.
CRIS-Team Scopus Importer:2023-04-20